If only I had told her - Nowlin, Laura (Naperville, Illinois : Sourcebooks Fire, 2024)
"Finn has always loved Autumn. She is a constant in his life, except it's in the role of friend, not girlfriend. Finn wants her to see him as more, wants to prove HE should be the man by her side. Even if that means heartache for the people they are each dating. It would be worth the pain to be with right person. Finn knows he and Autumn are fated to be together. But sometimes fate can be cruel to those in love"--
Keywords: Dating (Social customs) -- Fiction; Friendship -- Fiction; Teenagers -- Juvenile fiction; Dating -- Fiction; Love -- Fiction; Romance fiction